Location of electric vehicles charging stations for professionals : Mobiletric case - Dias, Rafael José Ferreira (2019)
The project developed for Mobiletric was conducted to improve one of their core business, ProStations, which is a network of electric vehicles charging stations hubs with exclusive access for professionals. The goal was to find the factors affecting the optimal locations for their new charging stations hubs. Mobiletric plans to be the market leader of this segment that is expected to increase exponentially from 2025 onward when the three major barriers for electric vehicles are overcome – price, range, and charging infrastructure. During the project, interviews were conducted to major players in the electric mobility industry with the purpose of better understanding the current dynamics of the market and questionnaires were conducted to potential clients – electric vehicles drivers. We found out that the optimal location for new fast-charging stations in Lisbon is close to main roads and usual routes, like home-work route or TVDE drivers usual working routes. When compared with the distance to the center (Terreiro do Paço), those charging stations should be located in the peripheries of the city, with a distance, on average, between 4,5 kilometers and 5,5 kilometers to that center. However, drivers value more the charging station being available than its location (availability over location) and are not price-sensitive due to the lack of fast-charging infrastructure in the city.